(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Atypical pneumonia is a disease of the respiratory system, which is one of the most common hospitalizations for children, which is manifested by a cough with scanty sputum, symptoms of intoxication, and changes in the lungs. The purpose of the scientific work: to study the effectiveness of the drug Resistol in the treatment of atypical pneumonia in children. We treated 60 children aged 12 months to 10 years, who were divided into 2 groups. The second group was prescribed Resistol. Resistol, a herbal preparation containing pelargonium root extract, is an effective immunomodulatory, antibacterial, antiviral drug that prevents the penetration of viruses and bacteria into the body.